Immunomodulatory Effects of Angelica Sinensis Polysaccharides on Juvenile Chinese Sturgeon (Acipenser sinensis): Physiological and Molecular Insights - Jianming Zhang; Tian Tian; Dezhi Zhang; Rui He; Debin Shu; Wei Jiang; Yacheng Hu (Fishes, 2025)
The Chinese sturgeon (Acipenser sinensis) is a critically endangered species with significant ecological and economic value. This study investigates the effects of Angelica sinensis polysaccharides (ASPs) on the antioxidant and immune responses of juvenile Chinese sturgeon through physiological and molecular approaches. Healthy juvenile Chinese sturgeon (n = 120, mean body weight 356.50 ± 92.87 g) were fed diets supplemented with 0%, 0.5%, 1.0%, and 2.0% ASP for 36 days. Results showed that ASP, particularly at 2.0%, significantly enhanced serum antioxidant capacity by increasing activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) and reduced malondialdehyde (MDA) content. Immune indices, including immunoglobulins (IgG and IgM), complement components (C3 and C4), lysozyme (LSZ) activity, and antimicrobial peptides (AMPs), were also significantly elevated in the 1.0% and 2.0% ASP groups. Transcriptome sequencing of spleen and kidney tissues from the control and 2.0% ASP groups identified 151 and 467 differentially expressed genes (DEGs), respectively, with significant enrichment in immune-related pathways such as phagocytosis and the MAPK signaling pathway. Ten candidate immune-related genes (e.g., PDIA4, H-2Q9α, TTC39B) were validated by qRT-PCR, confirming the reliability of the RNA-seq data. This study demonstrates that ASP can enhance the antioxidant and immune responses of juvenile Chinese sturgeon, providing a potential natural immunostimulant for aquaculture. These findings offer a scientific basis for the conservation and sustainable production of this endangered species and highlight the need for further research on the application of ASP in sturgeon aquaculture.